Effect of thixotropy and segregation on centrifuge modelling. Issue 4 (December 2012) - Sorta, Amarebh R.; Sego, David C.; Wilson, Ward
Abstract : In this paper, segregation related to the application of high centrifugal acceleration and the effect of thixotropy in modelling the settling behaviour of slurry/soft soils using a centrifuge are examined. Settling column and centrifuge tests were conducted on slurry/soft soils at various sand fines ratios (SFR) to define a segregation boundary using the ternary diagram. A segregation boundary based on centrifuge and settling column tests are established and the results indicate that the application of high gravity in centrifuge tests prompts and enhances segregation. It is also found that the segregation boundary of high gravity tests is a function of applied acceleration level, grain size of sand, the percentage fines and clay contents. The application of formulas that estimate the maximum size of sand that remain in suspension are evaluated and found conservative at high gravity tests. The shear strength of slurry/soft soils at various SFR and age were evaluated to assess the effect of non-gravity, time-dependent behaviour on strength and settling behaviour of slurry/soft soils. The results of the shear strength tests at various ages and composition indicate that strength gain is mainly due to thixotropy. The gain in shear strength due to thixotropy may not be properly modelled in centrifuge testing and may create difficulty in extrapolating centrifuge test results to prototype.